Noninvasive management for iatrogenic splenic injury caused by chest tube insertion: a case report. Issue 12 (28th October 2016) - Ohtaka, Kazuto; Hase, Ryunosuke; Chiba, Ryohei; Miyasaka, Mamoru; Sato, Shoki; Shoji, Yasuhito; Ichimura, Tatsunosuke; Senmaru, Naoto; Kaga, Kichizo; Matsui, Yoshiro
Key Clinical Message: Splenic injury is one of the most critical complications of chest tube insertion and often requires invasive emergency management. However, noninvasive management such as delayed removal of the malpositioned tube may be considered for a stable patient without severe adverse event. Abstract : Splenic injury is one of the most critical complications of chest tube insertion and often requires invasive emergency management. However, noninvasive management such as delayed removal of the malpositioned tube may be considered for a stable patient without severe adverse event.